2022
DOI: 10.3389/fcell.2022.809979
|View full text |Cite
|
Sign up to set email alerts
|

A Comprehensive Analysis of Fibrillar Collagens in Lamprey Suggests a Conserved Role in Vertebrate Musculoskeletal Evolution

Abstract: Vertebrates have distinct tissues which are not present in invertebrate chordates nor other metazoans. The rise of these tissues also coincided with at least one round of whole-genome duplication as well as a suite of lineage-specific segmental duplications. Understanding whether novel genes lead to the origin and diversification of novel cell types, therefore, is of great importance in vertebrate evolution. Here we were particularly interested in the evolution of the vertebrate musculoskeletal system, the mus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 139 publications
0
4
0
Order By: Relevance
“…Mucocartilage, which is now considered homogenous for fibrillar collagens (Root et al, 2022), consists of mucopolysaccharides and mesenchyme and is once considered a unique tissue for larval lampreys (Wright & Youson, 1982). A recent study systematically revealed the evolution of the collagen gene family in vertebrates and showed cyclostome-specific gain or loss of genes (Root et al, 2022). Hence, true cartilage in vertebrates can be considered as consisting of type II collagen fibers and chondrocytes.…”
Section: Diversity Of Cartilaginous Skeletons In Chordatesmentioning
confidence: 99%
See 3 more Smart Citations
“…Mucocartilage, which is now considered homogenous for fibrillar collagens (Root et al, 2022), consists of mucopolysaccharides and mesenchyme and is once considered a unique tissue for larval lampreys (Wright & Youson, 1982). A recent study systematically revealed the evolution of the collagen gene family in vertebrates and showed cyclostome-specific gain or loss of genes (Root et al, 2022). Hence, true cartilage in vertebrates can be considered as consisting of type II collagen fibers and chondrocytes.…”
Section: Diversity Of Cartilaginous Skeletons In Chordatesmentioning
confidence: 99%
“…The major differences between the skeletal systems of gnathostomes and cyclostomes are (1) absence of bone in cyclostomes and (2) evolution of new proteins in cyclostomes (lamprin, myxinin, and pharymprin) in addition to collagen fibers (Root et al, 2022). Lamprin is an elastin‐like fiber expressed in annular, trabecular, and piston cartilage but not in branchial and pericardial cartilages (Fernandes & Eyre, 1999; McBurney & Wright, 1996; Robson et al, 2000).…”
Section: Diversity Of Cartilaginous Skeletons In Chordatesmentioning
confidence: 99%
See 2 more Smart Citations